Sequence Planning and Tool Selection for Bending Processes of 2.5D Sheet Metals. (19th August 2014) - Lin, Alan C.; Chen, Chao-Fan
Abstract : Planning of an appropriate bending sequence is one of the most important aspects in the processing of sheet metals as the appropriateness of the plan affects correct selection of bending tools and feasibility of bending processes. This study aims to propose a set of principles to be followed for the planning of bending sequences and selection of bending tools for 2.5D sheet metals. To this end, we first define basic bending patterns by characterizing each pattern with a set of operation rules. The sheet metal is then decomposed into a series of bending patterns that is in turn used in the planning of bending sequences. In order to select the bending tools, we combine the contours of each bending operation, choose appropriate bending punches from the bending-tool database, and then undertake an interference check with the bending contours.